PELATIHAN BAHASA INGGRIS UNTUK ANAK DARI PARA IBU YANG SEDANG MENDAPATKAN PENYULUHAN DAN PENCEGAHAN DEMAM BERDARAH - surip Haryani; Rania Nadhita Rahman (LPPM STIKES Madani, 2022)
ABSTRACT The mothers in Karangploso received counseling related to dengue fever due to the emergence of dengue fever cases. The mothers who received counseling mostly brought their children during the counseling. The team initiated to give treatment to the children by giving them a training during the activity so that the mothers could receive counseling with full concentration. The special treatment given to their children was by providing English language training. English training was provided with the concept of English for kids. The training was given on Friday, September 10, 2021, at 08.30 – 12.00 at the early childhood education hall and RA Bunayya ICBB. The training participants were children from the binbaz housing complex with a total of 17 participants. They were provided guidance in understanding everyday vocabulary for children by providing simulated examples of how to read the vocabulary and asking children to follow the examples given. It is hoped that this training and mentoring will provide great benefits for children in recognizing and mastering English.